PERTANGGUNGJAWABAN ADVOKAT TERHADAP PRODUK LEGAL OPINION YANG BERISI KESESATAN HUKUM SEBAGAI BENTUK PENEGAKKAN KODE ETIK ADVOKAT - Kornelius, Yusuf; Lewoleba, Kayus Kayowuan (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
An advocate has the right to immunity in carrying out his profession by the professional code of ethics. However, there are problems regarding how lawyers are held accountable for mistakes when providing legal services such as making legal opinions that contain legal errors. Research was conducted to answer the legal problems that arise. This research utilizes normative legal research from statutory regulations, journals, and relevant news in the mass media. The research results show that giving a misleading legal opinion violates the ethics of honesty held by advocates, and the party harmed by a legal opinion can seek accountability through a lawsuit or complaint. Thus, even though advocates have immunity, they can still be held responsible for mistakes in making legal opinions they make. Keywords: Advocate; Legal opinion; Code of Ethics